ANALISIS KESALAHAN PENGGUNAAN HURUF KAPITAL DALAM KARANGAN BAHASA INDONESIA - Mahfudhoni, Elfa; Ari Pratiwi, Ika; Darmuki, Agus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research discusses spelling errors that are often experienced by elementary school students. These errors usually occur when writing an essay. Errors that often occur in writing essays are errors in the use of capital letters and punctuation. Spelling is a set of guidelines or standards that must be followed when writing so that readers can understand sentences and writers can achieve the desired goals. This research uses qualitative research with descriptive research. The subjects in this research were class IV students, class IV teachers. Data collection techniques in this research used observation, interviews and documentation techniques. The data analysis technique used is reading markers. The results of this research prove that there are still 4 students who still use capital letters incorrectly in people's names and place names. Efforts to reduce errors in using capital letters and punctuation in writing essays are 1) literacy, 2) Writing practice, 3) teaching basic rules for using capital letters and punctuation. This research should be used as a basis for students' attention and knowledge in using capital letters and punctuation in Indonesian language learning.